Analysis of Kancil's Car Knuckle Prototype - Soemardi, Tresna P.; Mahmudah, Aida (UI Scholars Hub, 2004)
Analysis of Kancil’s Knuckle Prototype. The objective of this work is to execute strength analysis of knuckle, which is made from FCD 50, by using static analysis on maximum loading. This maximum loading is obtained from front axle loading calculation on particular operating condition. That is, vehicle is braking while cornering in down hill. From previous vehicle loading calculation, we get a number of loading values on different speed and deceleration. At the end, we get a value of speed and deceleration that guarantee the vehicle safety if it is braking while cornering in down hill. As comparison, loading calculation is executed too for same operating condition on level ground. This is because of different deceleration for each operating condition, 0,5g for operating condition on downhill and 0,2g on level ground. The result shows that maximum loading occurred when vehicle is operated on down hill is larger than on level ground. Study of static focused on quantitative description of loads that act on technical structure in equilibrium.